1976
DOI: 10.1037/0278-7393.2.6.759
|View full text |Cite
|
Sign up to set email alerts
|

Constructive processes in simple linear-order problems.

Abstract: What are the processes involved in constructing a linear order from a set of relations between pairs of elements in the order? Subjects were presented with sets of digit pairs and instructed to form a single digit string on the basis of the order relations expressed by the pairs; for example, given 57, 19, 71, the correct response is 5719. Manipulations of presentation order revealed constructive processes of varying difficulty depending on whether a pair has zero, one, or two digits in common with the digits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
59
0
1

Year Published

1977
1977
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 9 publications
(9 reference statements)
11
59
0
1
Order By: Relevance
“…Examination of the recall data in Smith and Foos (1975) and Foos et al (1976) shows that the linear order equivalent of our canonical organization gives higher recall than any of the other orders. Linear orders that correspond to our backward and flashback organizations show roughly equivalent recall.…”
Section: Linear Ordering and Discourse Organizationmentioning
confidence: 89%
See 1 more Smart Citation
“…Examination of the recall data in Smith and Foos (1975) and Foos et al (1976) shows that the linear order equivalent of our canonical organization gives higher recall than any of the other orders. Linear orders that correspond to our backward and flashback organizations show roughly equivalent recall.…”
Section: Linear Ordering and Discourse Organizationmentioning
confidence: 89%
“…Within this literature, there is one set of studies that seems to tap many of the same psychological processes as the experiment in this article. These experiments used an arbitrary underlying linear ordering (as in the previous example) and studied all possible orderings of the three pairs (Foos, Smith, Sabol, & Mynatt, 1976;Smith & Foos, 1975). Thus, if this example is represented as AB, BC, CD, then this ordering of the three pairs is equivalent to our canonical discourse organization.…”
Section: Linear Ordering and Discourse Organizationmentioning
confidence: 99%
“…On the other hand, linear orderings are generally presented in a sequential order. Foos et al (1976) have shown that it is more difficult for subjects to construct an integrated representation from a nonsequential or "nonmatch" presentation order than from a sequential or "match" presentation order. Thus, it was necessary to rule out this factor in comparing the acquisition of a partial ordering with that of a linear ordering.…”
Section: Discussionmentioning
confidence: 99%
“…No matter how the items are presented, there must be some adjacently presented pairs that do not contain a common element. Foos, Smith, Sabol, and Mynatt (1976) have demonstrated that it is more difficult to construct an integrated array from a nonsequential or "nonmatch" presentation order than from a sequential or "match" presentation order. Thus, the difficulty in constructing complex partial orderings may arise from the difficulty found in constructing any arrays containing a nonmatch component.…”
mentioning
confidence: 99%
“…The purpose of this manipulation was to prevent the subject from viewing the third pair just long enough to read it and then pressing for the recall signal without engaging in any constructive processes. Under the present procedure, the subjects never knew whether the third pair would be followed by a recall Foos et al (1976). signal or another pair.…”
Section: Methodsmentioning
confidence: 95%